Design and Validation of an Educational Excellence and Human Resource Development Model for the Ministry of Education (Case Study: Golestan Province) - Safari, Mahboubeh; Safari, Maryam; Esmaeilnia Shirvani, Kambiz (Assessment and Practice in Educational Sciences, 2025)
The purpose of the present study was to design and validate a model of educational excellence and human resource development for the Ministry of Education in Golestan Province. The research adopted a mixed-methods approach (qualitative–quantitative), was applied and descriptive in nature, and was conducted using a cross-sectional survey method. The statistical population in the qualitative phase consisted of experts in the field of educational excellence, and in the quantitative phase included all employees of the Ministry of Education in Golestan Province. The sampling method in the qualitative phase was snowball sampling, and in the quantitative phase simple random sampling was used. The qualitative sample size reached 10 participants upon achieving theoretical saturation, and the quantitative sample size was determined to be 297 individuals based on Morgan’s Table. The data collection tool in the qualitative phase was a semi-structured interview, and in the quantitative phase a researcher-made questionnaire was used. Data were analyzed using Structural Equation Modeling (SEM) via PLS software. The results indicated that the final criteria consisted of 12 main categories and 37 subcategories. Based on the Interpretive Structural Modeling (ISM), the category of “Human Resource Development” was placed at the first level; the category of “Educational Excellence” at the second level; the categories of “Educational, Promotional, and Research Activities” at the third level; the categories of “Policy-Making” and “Systematic Process” at the fourth level; the category of “Higher Education System” at the fifth level; the categories of “Individual Factors” and “Cognitive-Social Characteristics” at the sixth level; and the categories of “Contextual Factors” and “Structural Factors” at the seventh level. Furthermore, the model fit assessment indicated that the coefficient of determination for the endogenous constructs of the research model was satisfactory. The coefficient of determination for Human Resource Development was reported as 0.653, which is an acceptable value. Similar acceptable values were obtained for all research categories. The variable values generally ranged from 0.15 to 0.35 or greater than 0.35. Therefore, the predictive power of the research categories is estimated to be moderate to strong.